Cardiac Troponin Composition Characterization after Non ST-Elevation Myocardial Infarction: Relation with Culprit Artery, Ischemic Time Window, and Severity of Injury. (22nd November 2020) - Damen, Sander A J; Cramer, Gilbert E; Dieker, Hendrik-Jan; Gehlmann, Helmut; Ophuis, Ton J M Oude; Aengevaeren, Wim R M; Fokkert, Marion; Verheugt, Freek W A; Suryapranata, Harry; Wu, Alan H; van Wijk, Xander M R; Brouwer, Marc A
Abstract: Background: Troponin composition characterization has been implicated as a next step to differentiate among non-ST elevation myocardial infarction (NSTEMI) patients and improve distinction from other conditions with troponin release. We therefore studied coronary and peripheral troponin compositions in relation to clinical variables of NSTEMI patients. Methods: Samples were obtained from the great cardiac vein (GCV), coronary sinus (CS), and peripheral circulation of 45 patients with NSTEMI. We measured total cTnI concentrations, and assessed both complex cTnI (binary cTnIC + all ternary cTnTIC forms), and large-size cTnTIC (full-size and partially truncated cTnTIC). Troponin compositions were studied in relation to culprit vessel localization (left anterior descending artery [LAD] or non-LAD), ischemic time window, and peak CK-MB value. Results: Sampling occurred at a median of 25 hours after symptom onset. Of total peripheral cTnI, a median of 87[78-100]% consisted of complex cTnI; and 9[6-15]% was large-size cTnTIC. All concentrations (total, complex cTnI, and large-size cTnTIC) were significantly higher in the CS than in peripheral samples ( P  <   0.001). For LAD culprit patients, GCV concentrations were all significantly higher; in non-LAD culprit patients, CS concentrations were higher. Proportionally, more large-size cTnTIC was present in the earliest sampled patients and in those with the highest CK-MB peaks. Conclusions: In coronary veins draining the infarct area, concentrations of both full-size and degraded troponin were higher than in the peripheral circulation. This finding, and the observed associations of troponin composition with the ischemic time window and the extent of sustained injury may contribute to future characterization of different disease states among NSTEMI patients.